Tense harmony Thai cinema and popular music - Jaiser, Gerhard (2018)
Access online through this link: https://www.plarideljournal.org/article/tense-harmony-thai-cinema-and-popular-music
Keywords: Motion pictures -- Thailand; Popular music -- Thailand; Motion picture music